Understanding the role of visuo-spatial working memory in adult mathematics - Hubber, Paula Jane (2015)
Mathematics is an important part of everyday adult life and requires skilled use of a variety of cognitive resources. The aim of this thesis was to explore the use of working memory in adult mathematics performance and particularly the role of visuo-spatial working memory. In the first study, differences in working memory capacity between skilled adult mathematicians and those who have less expertise in mathematics were investigated. This involved the use of working memory span tasks that included a novel processing element that was as neutral as possible with regard to the verbal and visuo-spatial storage elements. The results of this study included the novel finding that skilled adult mathematicians have a superior ability to store visuo-spatial information within working memory whilst concurrent processing is taking place. In the second study, measures of basic temporary visuo-spatial storage and endogenous spatial attention were used to discover whether these abilities drive the differences in visuo-spatial working memory capacity between skilled mathematicians and non-mathematicians found in Study 1. Results included the novel finding that capacity differences are not explained by basic temporary storage or endogenous spatial attention. The relationships of visuo-spatial item memory and order memory with adult mathematics were then explored in Study 3. Results showed the ability to order visuo-spatial information, rather than memory for whether a visuo-spatial item is simply present, seems to be related to adult mathematics achievement. Working memory capacity differences were again investigated in Study 4, in which the processing elements within the span tasks were of a more traditional verbal and visuo-spatial nature. Differences between mathematicians and non-mathematicians for general visuo-spatial ability were also examined to see whether this ability drives the relationship between visuo-spatial working memory capacity and adult mathematics performance. Contrary to the results of Study 1, mathematicians did not have superior working memory capacity to non-mathematicians in any combination of verbal and visuo-spatial storage and processing. Mathematicians therefore only seem to have superior visuo-spatial working memory capacity when the executive resources used during processing are comparatively low, as in Study 1. Adult mathematicians were also found to have superior general visuo-spatial ability to non-mathematicians, but this did not explain observed working memory capacity differences. Finally, Study 5 explored the relative roles of the visuo-spatial sketchpad and central executive components of visuo-spatial working memory when adults solve arithmetic using different strategies. Whilst both the central executive and visuo-spatial sketchpad are used in adult arithmetic, the former was found to be used to a greater extent and particularly when counting was used to solve problems.